Validity Test of Happiness at Work Construct Adaptation in Employees in Indonesia - Wulandri, Desi; Batubara, Megawati (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The construct of happiness at work is very important in research related to human resource management. Testing the reliability and construct validity of the happiness at work scale is important to measure and assess happiness at work in employees in Indonesia. This study aims to collect evidence of the validity of the internal structure of the Indonesian version of happiness at work. The study involved 297 active employees in private companies, state-owned enterprises, government agencies and other institutions in Indonesia, through online questionnaire completion. Data were analyzed using Confirmatory Factor Analysis (CFA) on a 31-item measuring instrument. Reliability of 31-items using Cronbach's Alpha is 0.949 with goodness of fit values (RMSEA 0.079, CFI 0.97 and NNFI 0.97) after modification. It can be concluded that the 31 favorable items can be used to measure happiness at work’s employees in Indonesia.Konstruk happiness at work atau kebahagiaan di tempat kerja menjadi sangat penting dalam penelitian terkait manajemen sumber daya manusia. Pengujian reliabilitas dan validitas konstruk happiness at work scale ini menjadi penting untuk mengukur dan menilai happiness at work pada karyawan di Indonesia. Studi ini bertujuan untuk mengumpulkan bukti validitas struktur internal happiness at work versi Bahasa Indonesia. Penelitian ini melibatkan 297 karyawan aktif di perusahaan swasta, BUMN, instansi pemerintahan dan lembaga lainnya di Indonesia, melalui pengisian kuesioner secara daring. Analisis data menggunakan Confirmatory Factor Analysis (CFA) terhadap alat ukur 31-item. Reliabilitas 31-item menggunakan Cronbach’s Alpha sebesar 0.949 dengan nilai goodness of fit (RMSEA 0.079, CFI 0,97 dan NNFI 0,97) setelah di modifikasi. Maka dapat disimpulkan bahwa 31 favorable item dapat digunakan untuk mengukur happiness at work pada karyawan di Indonesia.